Analisis Pengaruh Kepadatan Node terhadap Kinerja Protokol Routing DYMO dan DSR Pada Mobile Ad-Hoc Network (MANET) - Muhammad Syaifuddin FP; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile ad-Hoc Nertwork (MANET) is a technology that has the ability to adapt to the condition of mobile nodes. Each node has the same position that is doing a routing function that can determine and forward communication lines between nodes, so that a routing protocol is needed that can handle the exchange of data in providing an optimal routing path. The routing protocol used in this study is reactive routing, namely DYMO and DSR. The DYMO and DSR routing protocols route formation from the source node to the destination node based on the request of the source node. This study using Network Simulator 2.35 with a node density scenario using variations in the number of nodes totaling 50 nodes to 200 nodes with multiples of 10 nodes, and variations in data packet size using packet sizes of 512 bytes and 1024 bytes. Performance is measured based on average throughput, end to end parameters delay, packet loss, and average jitter with the best values in a row are 101.45 KBps in the data packet size of 512 bytes, 44.26 ms in the data packet size of 512 bytes, 2.36% in the size of a 512 bytes data packet, 1.72 ms in the data packet size of 512 bytes. These results were obtained on the DYMO routing protocol, so it can be concluded that the DYMO routing protocol has better performance than DSR in the aspect of node density with different packet size variations.